Justin Bieber: a jornada contada pelos meios de comunicação - Reis, Aline Lima (Brasil, 2022)
In an increasingly connected world, the online universe allows people to share their talents with thousands of internet users, and thus gain admirers or even legions of loyal fans. It is not common, but it happens, and when a "star" is discovered on the Internet it is something that is highlighted in all media. This paper aims to present an analysis of two key points in the career of singer Justin Bieber: the period between 2013 and 2014, when his image was compromised due to various controversies, and the years 2015 and 2016, when the singer released his fourth studio album, which was acclaimed by critics and the general public worldwide. This is a research with elements of narrative, exploratory with qualitative approach, conducted through analysis of the trajectory of Justin Bieber narrated by the media, based on the Hero's Journey.